Reflecting on the Possibilities of Religious Education Research - Winings, Kathy (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This resource provides six articles noting current directions in religious education research. The field of religious education can be very broad and is capable of addressing a wide range of issues. This resource looks at six specific cases. First, a new educational tool that allows students to self-reflect on their religious and worldview journey is presented. A second contribution looks at a quantitative study of how adolescents view religion in Spain, utilizing analytical, empirical and social research methods. A critical component that is studied in this context is gender. The third article presents a creative look at how the Tauhidic elements in Islamic religious education can contribute to understanding the environmental challenges we face, looking at how we can be encouraged to take appropriate action to resolve our ecological problems. The fourth article looks at the suitability of religious education in a post-pandemic world in developing discussions on values, and how students can make sense of which values are right for them within the range of competing values. The fifth article also looks at life in a post-pandemic world. As thousands of families and individuals have experienced first-hand the pain of long-term illness and loss, understanding trauma-informed pedagogies can be extremely valuable. The sixth and final contribution looks at the value of using digital stories to foster global interreligious understanding, as well as deeper theological and spiritual understanding, especially in a world that is saturated with media and devices. Overall, the articles reflect a range of perspectives and research interests in the field of religious education.